2007
DOI: 10.2350/06-06-0119.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pancreatic Carcinoma Metastatic to the Placenta: A Case Report and Literature Review

Abstract: In this article, we report a case of maternal pancreatic carcinoma metastatic to the placenta. The baby is alive and well, with no evidence of tumor metastasis at the age of 1 year. We also present a comprehensive review of all maternal cancers with metastasis to the placenta and/or baby published in the English language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…Al-Adnani and colleagues [3] reviewed 81 cases of metastatic maternal tumors to the placenta and/or baby reported in the English language literature. We performed a comprehensive review of the English language literature and identified 32 other cases of fetal malignancy/TAM involving the placenta, with involvement specifically defined as circulating tumor cells and/or CV stromal infiltrates ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Al-Adnani and colleagues [3] reviewed 81 cases of metastatic maternal tumors to the placenta and/or baby reported in the English language literature. We performed a comprehensive review of the English language literature and identified 32 other cases of fetal malignancy/TAM involving the placenta, with involvement specifically defined as circulating tumor cells and/or CV stromal infiltrates ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1 in 1000 to 1 in 1500 pregnancies is complicated by maternal malignant disease but well‐documented reports of maternal cancer metastatic to the placenta are rare, and metastatic to the fetus, exceptionally rare. A review published at the end of the 1980s reported that between 1866 and 1989, 52 cases had been published in the international literature107, with around 20 more cases reported in the last 20 years or so7, 8, 108–119. Malignant melanoma affects young individuals and spreads extensively via the vascular system, and is therefore the most common maternal neoplasm involving the placenta, accounting for about one third of cases98, 107, with carcinomas of breast and bronchus becoming increasingly common.…”
Section: Placental Malignancymentioning
confidence: 99%
“…[123] Table 1 summarizes the existing case reports of pancreatic neoplasms during pregnancy. These tumors present a diagnostic and therapeutic challenge when diagnosed antepartum.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only eight reported cases of pancreatic adenocarcinoma,[1–8] thirteen cases of cystic pancreatic lesions diagnosed during pregnancy,[9–21] and three reported cases of pancreatic neuroendocrine tumors. [22, 23] Their occurrence during pregnancy leads to dilemmas in diagnosis, management, and timing of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation